Awaking N-hyperfine couplings in charged yttrium nitride endohedral fullerenes. Issue 39 (27th September 2017) - Zhao, Chong; Wang, Taishan; Li, Yongjian; Meng, Haibing; Nie, Mingzhe; Tian, Jianlei; Wang, Chunru
Abstract : Charged yttrium nitride endohedral fullerenes show particular N-hyperfine couplings that are sensitive to the outer carbon cage. Abstract : The electron spin properties of endohedral metallofullerene molecules have broad potential applications in quantum information and magnetic induction systems due to the high stability and sensitivity. Herein, we synthesized a series of Y3 N@C2 n ( n = 40–44) molecules and studied the hyperfine structures of their anion radicals via ESR measurements and DFT calculations. N-Hyperfine couplings were clearly observed in the ESR spectra of charged Y3 N@C80 and Y3 N@C86 anion radicals, which are not found in the other metallofullerenes. The ESR results revealed size-dependent spin distributions and hyperfine structures, which are sensitive to subtle changes in the carbon cage and the configuration of the yttrium nitride cluster. BOMD cluster trajectories simulations indicated that the Y3 N cluster almost rotates freely in neutral Y3 N@C80 but there is a certain degree of limitation in the Y3 N@C80 anion.